Resonances in the Realm of Intercultural Music Education: Insights from Multi-sited Fieldwork - Peres, Maria; Didier Sarrouy, Alix; Castro, Ricardo (Schweizer Jahrbuch für Musikwissenschaft, 2026)
This short article by the RESONANCES project research team explores the starting point of how, based on the first insights from multi-sited fieldwork, intercultural encounters through music education may create connectivity and meaningful shared experiences. For 18 months, this research project, funded by the Haute école de musique de Genève (HEM) and the Portuguese Instituto de Etnomusicologia - Centro de Estudos de Música e Dança (INET-md), is led by Ricardo Castro, with Alix Didier Sarrouy as scientific coordinator, and Maria Peres as research assistant.